Study on Simulators of Pancreatic Adenocarcinoma: An Approach to Avoid Misdiagnosis - Atanas Dimitrov Hilendarov; Alexandar Asenov Georgiev; Lyubomir Georgiev Chervenkov (Highlights on Medicine and Medical Science Vol. 8, 2021)
To present examination finding of neoplastic, inflammatory and benign pancreatic as well as non-pancreatic processes that can simulate pancreatic adenocarcinoma. Adenocarcinoma of the pancreas (PA) is one of the most aggressive malignancies, the fourth leading cause of cancer-related deaths in the Western world. Focal fatty infiltration is usually most pronounced in the head of the pancreas and at contrast enhancement in CT usually appears as a region with reduced contrast matherial amplification compared to normal pancreatic tissue simulating PA. Imaging of a hypoathenuating lesion in the head of the pancreas corresponds to adenocarcinoma in most cases. However, radiologists should be careful, because a false positive diagnosis can lead to unnecessary surgery, which is not without complications.